2020
DOI: 10.21608/ejprs.2020.68177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet Rich Plasma (PRP) on Bone Graft in Alveolar Cleft Repair

Abstract: Background: Ultimate repair of alveolar defects is a great challenge in practical field, many bone graft materials have been evolved in the literatures for alveolar defect reconstruction as autogenous, allogenic, xenogenic, and alloplastic grafts [1], autogenous iliac crest bone graft is the gold standard among other graft materials evaluated. However, the procedure associated with a potential risk of early complications such as graft resorption, graft leakage, infection, or graft failure, failure rate is abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In another study, alveolar clefts and bone defects created by removing mandibular lesions were also treated with autologous bone mixed with PRP, using as control group patients whose bone defects were grafted with autologous bone alone. As expected, lesions treated with PRP showed more bone growth than controls after 12 months of surgery. , …”
Section: Bioactive Factors Incorporated Into Scaffolds Stimulate Cmf ...supporting
confidence: 79%
See 1 more Smart Citation
“…In another study, alveolar clefts and bone defects created by removing mandibular lesions were also treated with autologous bone mixed with PRP, using as control group patients whose bone defects were grafted with autologous bone alone. As expected, lesions treated with PRP showed more bone growth than controls after 12 months of surgery. , …”
Section: Bioactive Factors Incorporated Into Scaffolds Stimulate Cmf ...supporting
confidence: 79%
“…As expected, lesions treated with PRP showed more bone growth than controls after 12 months of surgery. 163,164 In another clinical study, bilateral mandibular fractures were treated with a bone allograft containing autologous PRP in a patient whose psychiatric conditions impaired the obtention and use of autologous iliac bone. The fractures healed completely 36 months after treatment, supporting the utility of PRP to enhance bone repair.…”
Section: Bioactive Factors Incorporated Into Scaffolds Stimulate Cmf ...mentioning
confidence: 99%
“…Five studies reported immediate post‐operative complications like bleeding, pain, infection, discharge and wound dehiscence 26,29,32–34 . The closure of wound dehiscence with secondary healing in subsequent follow‐ups was also reported.…”
Section: Resultsmentioning
confidence: 99%
“…Among the RCTs, only two studies were of low risk, 27,41 while two were classified as unclear risk, 32,33 and three were high risk 26,31,42 (Figure 2A). Among two CCTs, one study was assessed to have moderate risk, 34 whereas the other was judged under serious risk of bias 29 (Figure 2B). The primary source of bias was the randomization method, allocation concealment, and selective reporting.…”
Section: Risk Of Bias Within the Studiesmentioning
confidence: 99%
“…Growth factors obtained from platelet rich plasma PRP was introduced with the advantages of promote tissue healing and accelerates recovery. PRP is proved enhances bone formation in alveolar clefts when admixed with iliac autologous bone graft as it leads to early bone formation, increased bone density, decreases bone resorption, low infection rate and least post-operative complications [25][26][27]. In the year 2006, platelet-rich fibrin (PRF) is introduced by Chokroun as the second generation concentrate of PRP [28].…”
Section: The Grafting Tissue Of Choicementioning
confidence: 99%